Cameroon's Infrastructure : A Continental Perspective - Dominguez-Torres, Carolina; Foster, Vivien (2012)
The poor state of Cameroon's infrastructure is a key bottleneck to the nation's economic growth. From 2000 to 2005, improvements in information and communications technology (ICT) boosted Cameroon's growth performance by 1.26 percentage points per capita, while deficient power infrastructure held growth back by 0.28 points per capita. If Cameroon could improve its infrastructure to the level of Africa's middle-income countries, it could raise its per capita economic growth rate by about 3.3 percentage points. Cameroon has made significant progress in many aspects of infrastructure, implementing institutional reforms across a broad range of sectors with a view to attracting private-sector participation and finance, which has generally led to performance improvements. But the country still faces a number of important infrastructure challenges, including poor road quality, expensive and unreliable electricity, and a stagnating and uncompetitive ICT sector. Cameroon currently spends around $930 million per year on infrastructure, with $586 million lost to inefficiencies. Removing those inefficiencies would leave an infrastructure funding gap of $350 million per year. Given Cameroon's relatively strong economy and natural-resource base, as well as its success in attracting private financing, the country should be able to close that gap and meet its infrastructure goals within 13 years.